Komsomol Activities in the Countryside During the NEP. Joseph Stalin’s Directives (1925) - Krzyżaniak, Michał (Sensus Historiae, 2021)
The text presents Joseph Stalin’s directives to members of the Communist Youth Union from 1925. The tasks entrusted to the youth were included in the speech by the USSR leader “About Komsomol activism in the countryside.” They are analyzed by the author of the article from the perspective of the then situation of the Soviet Union, where the NEP had already been implemented. The improved economic situation translated into a further process of indoctrination of young people and encouraging them to build the country under communist conditions.